1993
DOI: 10.1037/0735-7044.107.6.970
|View full text |Cite
|
Sign up to set email alerts
|

Emotion, novelty, and the startle reflex: Habituation in humans.

Abstract: Previous research with both animal and human subjects has shown that startle reflex magnitude is potentiated in an aversive stimulus context, relative to responses elicited in a neutral or appetitive context. In the present experiment, the same pleasant, unpleasant, and neutral picture stimuli were repeatedly presented to human subjects. Startle reflex habituation was assessed in each stimulus context and was compared with the habituation patterns of heart rate, electrodermal, and facial corrugator muscle resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
259
3
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(293 citation statements)
references
References 39 publications
28
259
3
3
Order By: Relevance
“…Of note, the postauricular reflex has also been shown to be resistant to habituation (Hackley et al, 2017), which contrasts with the startle eyeblink reflex (e.g., Bradley, Lang, & Cuthbert, 1993; Grillon & Baas, 2003; Hackley et al, 2017; Rimpel, Geyer, & Hopf, 1982) and SCR (e.g., Bradley et al, 1993; Hare, Wood, Britain, & Shadman, 1970) that are both sensitive to habituation, and is thus less affected by repetitive stimulus presentations, as is the case in human conditioning paradigms. In sum, the fact that we observed differential appetitive conditioning at the psychophysiological level with the postauricular reflex suggests that it provides a sensitive psychophysiological measure of human appetitive conditioning, probably even more sensitive than both the startle eyeblink reflex and SCR.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the postauricular reflex has also been shown to be resistant to habituation (Hackley et al, 2017), which contrasts with the startle eyeblink reflex (e.g., Bradley, Lang, & Cuthbert, 1993; Grillon & Baas, 2003; Hackley et al, 2017; Rimpel, Geyer, & Hopf, 1982) and SCR (e.g., Bradley et al, 1993; Hare, Wood, Britain, & Shadman, 1970) that are both sensitive to habituation, and is thus less affected by repetitive stimulus presentations, as is the case in human conditioning paradigms. In sum, the fact that we observed differential appetitive conditioning at the psychophysiological level with the postauricular reflex suggests that it provides a sensitive psychophysiological measure of human appetitive conditioning, probably even more sensitive than both the startle eyeblink reflex and SCR.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies utilizing on-line peripheral psychophysiological recording (e.g. electrodermal activity, eyeblink startle) will be needed to assess the viability of this interpretation as well as the potential interaction of arousal and valence in the present task, given their highly correlated nature [22]. That said, this study clearly shows that fMRI responses across the amygdaloid region will not be necessarily uniform [2,20,23], an effect predicted by animal research demonstrating differential functional roles across subregions and subnuclei of the amygdala (see [2] for discussion).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the presence of an unpleasant odour increases startle magnitude response (blink component) (Ehrlichman et al, 1995) and nociceptive withdrawal reflex (Bartolo et al, 2013); viewing an unpleasant picture increases the startle magnitude and viewing a pleasant one decreases it (Bradley et al, 1993); holding your hand near your face increases the hand-blink reflex triggered by median nerve stimulation at the wrist (Sambo et al, 2012a), an effect that is positively related to self-reported anxiety (Sambo and Iannetti, 2013) and that can be eliminated by placing a solid barrier, but not a fragile one, between the hand and the face (Sambo et al, 2012b). Moreover, this modulation of the hand-blink reflex according to how close the hand is to the face is modulated in a predictive fashion, being lower if the hand is moving away from the face than if it is moving towards the face (Wallwork et al, 2016).…”
Section: Reduced Reflex Threshold In People With Painmentioning
confidence: 99%
“…For example, the hand-blink reflex, triggered by electrical stimulation over the median nerve at the wrist, is larger when the stimulated hand is within the peripersonal space of the face (Sambo et al, 2012a) and this upregulation occurs in real time and, indeed, in a feedforward manner (Wallwork et al, 2016). The startle response can be modulated by factors such as the pleasantness/unpleasantness of odours (Ehrlichman et al, 1995) and by viewing emotionally salient images (Bradley et al, 1993). These reflexes, like the nociceptive flexion reflex (NFR), are clearly defensive in nature and upregulation in times of potential bodily threat would seem to offer some evolutionary advantage.…”
Section: Introductionmentioning
confidence: 99%